Chondroitin Sulfate-Modified Liposomes for Targeted Co-Delivery of Doxorubicin and Retinoic Acid to Suppress Breast Cancer Lung Metastasis - Zhiwei Zhang; Lixin Ma; Jingwen Luo (MDPI AG, 2021)
Breast cancer treatment remains challenging due to high levels of cell metastasis. Chemotherapy drug combinations can inhibit both tumor growth in situ and metastasis to distant organs. Therefore, here, we developed chondroitin sulfate liposomes (CSLs) as a carrier for the co-delivery of retinoic acid (RA) and doxorubicin (DOX) and examined their efficiency in suppressing lung metastasis of breast cancer. CSLs were prepared using CS-deoxycholic acid conjugates and found to encapsulate both RA and DOX via hydrophobic and hydrophilic interactions. The resulting DOX+RA-CSLs were uniformly spherical and showed good serum stability and encapsulation efficiency of 98.7% ± 1.3% for RA and 90.8% ± 2.9% for DOX. Pharmacodynamic experiments in vitro and in vivo also revealed that DOX+RA-CSLs had better anticancer and anti-metastatic activity than CS-free liposomes, single drug-loaded liposomes, and free drug solutions at the same dose (2 mg/kg DOX or RA). Our results suggest that this liposomal delivery system can effectively suppress lung metastasis of breast cancer.